2014
DOI: 10.7314/apjcp.2014.15.5.2309
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Novel Fusion Gene (HLA-E and HLA-B) by RNA-seq Analysis in Esophageal Squamous Cell Carcinoma

Abstract: Esophageal squamous cell carcinoma (ESCC) is the most common histologic subtype of esophageal cancer and is characterized by a poor prognosis. Determining gene changes in ESCCs should improve understanding of putative risk factors and provide potential targets for therapy. We sequenced about 55 million pair-end reads from a pair of adjacent normal and ESCC samples to identify the gene expression level and gene fusion. Sanger sequencing was used to verify the result. About 17 thousand genes were expressed in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(23 reference statements)
0
3
0
Order By: Relevance
“…Less than 10 studies of ESCC alterations by RNA-seq have been reported in the literature, most of which of Chinese patients and with similar number of patients to those included in our study [25], [26], [27], [28], [29], [30], [31]. These studies also showed different but comparable estimates of DEG (1425 to 6150) to our findings (6698), depending on sample size, fold-change and P value cutoffs, with a predominance of overexpression.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Less than 10 studies of ESCC alterations by RNA-seq have been reported in the literature, most of which of Chinese patients and with similar number of patients to those included in our study [25], [26], [27], [28], [29], [30], [31]. These studies also showed different but comparable estimates of DEG (1425 to 6150) to our findings (6698), depending on sample size, fold-change and P value cutoffs, with a predominance of overexpression.…”
Section: Discussionmentioning
confidence: 90%
“…Although enrichment of alterations of the Wnt pathway has been reported in ESCC studies with RNA-seq [7], [26], [27], this pathway had not been further explored. Our findings showed 54 DEG in the Wnt pathway, most of which showing overexpression and associated with activation of Wnt signaling.…”
Section: Discussionmentioning
confidence: 99%
“…[12,13] More importantly, numerous studies have revealed that HLA-II members are involved in cancers like ESCC. [1417] However, the association between HLA-DQA1 and ESCC in high-incidence area of northern China has not been well characterized.…”
Section: Introductionmentioning
confidence: 99%